PEMODELAN SENYAWA TURUNAN ASAM KARBAMAT SEBAGAI SENYAWA ANTIKANKER MENGGUNAKAN METODE SEMIEMPIRIS AM1 - Senny Widyaningsih; Purwati Purwati; Riyadi Riyadi (Universitas Jenderal Soedirman, 2007)
4-N-carbamic acid-4’-dimetylpipodopylotoxin and its derivatives are compounds which are synthesized from etoposide (VP 16). These compounds are used as anticancer medicine because they inhibit DNA topoisomerase II enzyme. The enzyme participates in controlling breaking process of DNA double helix bounding in cancer cell. It makes cancer growing cease and dies because cell can not replicate. However, the compound insoluble in water, make a medicine resistant, inhibit metabolism system and poison. It needs to design a modification of new compounds from carbamic acid derivatives which have higher activity. Structure modification was done using Quantitative Structure Activity Relationship (QSAR) which was a computational chemistry application in medicine design process. This research used semiempiris AM1 method to determine the best QSAR equation based on multilinear regression analysize, with log 1/IC50 as dependent variable and independent variables were atomic net charge of qN29, qC30, qO31, qO32, dipole moment, n-octanol-water coefficient partition (Log P), and polarity. The best QSAR equation in this research was : Log 1/IC50 = 4.871 + 12.738 qN29 + 33.183 qC30 + 28.015 qO31 – 3.6 x 10-2 polarity, with N = 13, r =0.907, SE = 0.13025, Fcount/Ftable = 1.901, PRESS = 0.1357. Based on the best QSAR equation, the prediction compounds were 1, 2, 3, 8, and 22 with each IC50 theoretical value were 0.032, 0.034, 0.036, and 0.098 µM.